1992
DOI: 10.3349/ymj.1992.33.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Multiple basal cell carcinoma associated with keratoacanthoma

Abstract: We report a case of multiple basal cell carcinoma associated with keratoacanthoma. A 65-year-old Korean female had suffered from multiple, variable-sized papules and nodules on the face for 20 years previous to treatment. She had no history of arsenic intake, irradiation, herb medication, or hereditable or preexisting dermatoses. Histopathologically, the tumors revealed typical findings of solid and adenoid types of basal cell carcinoma and keratoacanthoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…2 Around the world, primary and secondary prevention efforts for melanoma have produced conflicting results. While some groups have shown that screening was effective in increasing the proportion of thin tumors, 1013 stabilizing the incidence of thick tumors, 11,14 and improving survival, 13,15 others have shown that the proportion of thick IMMs and fatal incidence has remained unaffected by screening efforts. 3,12,14,1619 …”
Section: Introductionmentioning
confidence: 99%
“…2 Around the world, primary and secondary prevention efforts for melanoma have produced conflicting results. While some groups have shown that screening was effective in increasing the proportion of thin tumors, 1013 stabilizing the incidence of thick tumors, 11,14 and improving survival, 13,15 others have shown that the proportion of thick IMMs and fatal incidence has remained unaffected by screening efforts. 3,12,14,1619 …”
Section: Introductionmentioning
confidence: 99%
“…Nonsyndromic, but hereditary multiple BCCs have been reported in literatures, but they were ruled out based on the negative family history [ 9 ]. There was no history of exposure to arsenic, irradiation, dry ice and no evidence of keratoacanthoma or xeroderma pigmentosum [ 10 11 ]. Cytochrome P450 (CYP2D6) genotypes and Glutathione S transferase (GSTM1 and GSTT1) are included with a multiple presentation phenotypes of BCC and have been introduced in the literature [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Individuals with blonde hair, blue eyes have increased risk of developing basal cell carcinoma. 5,7,[9][10][11][12][13][14][15][16][17] Basal cell carcinoma is a slow-growing tumor of non-keratinizing cells originating in the basal layer of interfollicular epidermis. 2 It is rarely metastasizing tumour with the rate of metastasis being <0.1 per cent.…”
Section: Introductionmentioning
confidence: 99%